Submit a question to our community and get an answer from real people.
Submit

what is
-3(x-9)=6?

Report as

First, distribute the -3 to the values in the parantheses.
-3x + 27 = 6

Subtract 27 from both sides.
-3x = -21

Divide both sides by -3.
x = 7

Helpful (3) Fun Thanks for voting Comments (0)
Report as
Add a comment...

-3(x-9)=6
/-3. /-3
x-9=-2
+9. +9
X=7

Helpful (2) Fun Thanks for voting Comments (0)
Report as
Add a comment...
Do you have an answer?
Answer this question...
Did you mean?
Login or Join the Community to answer